Novel quasi-autothermal hydrogen production process in a fixed-bed using a chemical looping approach: A numerical study. (1st June 2017) - Diglio, Giuseppe; Bareschino, Piero; Mancusi, Erasmo; Pepe, Francesco
Abstract: This paper presents a novel quasi -autothermal hydrogen production process. The proposed layout couples a Chemical Looping Combustion (CLC) section and a Steam Methane Reforming (SMR) one. In CLC section, four packed-beds are operated using Ni as oxygen carrier and CH4 as fuel to continuously produce a hot gaseous mixture of H2 O and CO2 . In SMR section, two fixed-beds filled with Ni-based catalyst convert CH4 and H2 O into a H2 -rich syngas. Four heat exchangers were employed to recover residual heat content of all the exhaust gas currents. By means of a previously developed 1D numerical model, a dynamic simulation study was carried out to evaluate feasibility of the proposed system in terms of methane conversion (100% circa), hydrogen yield (about 0.65 molH2 /molCH4 ) and selectivity (about 70%), and syngas ratio (about 2.3 molH2 /molCO ). Energetic and environmental analyses of the system performed with respect to conventional steam methane reforming, highlights an energy saving of about 98% and avoided CO2 emission of about 99%. Graphical abstract: Highlights: A quasi -autothermal H2 production process was proposed and numerically studied. A continuous H2 -rich syngas stream can be produced by the proposed system. Lower energy demand was evaluated with respect to traditional systems. The proposed system has near-zero CO2 emissions.